ASEISMIC PERFORMANCE OF REINFORCED CONCRETE INFILL FRAME - KESAVARATHNAM, V.; DEVI, Dr. G. NANDINI; BABU, Dr. S. SURESH (IJRDO - Journal of Mechanical And Civil Engineering, 2016)
Moderate and severe earthquakes have struck different places in the world, causing severe damage to reinforced concrete structures. Earthquake often effect the bond between the structural elements and masonry in-fills of the building. Masonry in-fills are often used to fill the void between horizontal and vertical resisting elements of the building frame. An infill wall enhances considerably the strength and rigidity of the structure. It has recognized that frames with infills have more strength and rigidity in conditions. Hence the studies about the behaviour of 3D- frames with or without masonry in-fills are necessary.